2021
DOI: 10.1002/pd.6024
|View full text |Cite
|
Sign up to set email alerts
|

Increased nuchal translucency after low‐risk noninvasive prenatal testing: What should we tell prospective parents?

Abstract: Three decades ago, the observation that first trimester fetuses with excess fluid accumulation at the back of the neck were more likely to be aneuploid, gave rise to a new era of prenatal screening. The nuchal translucency (NT) measurement in combination with serum biomarkers and maternal age, resulted in the first trimester combined screening (FTCS) program. The introduction of noninvasive prenatal testing (NIPT) over the past decade has introduced the option for parents to receive highly sensitive and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…We select the cases with reference to the updated eligibility criteria from overseas programs (e.g., National Health Service (England) [ 25 ]) and professional society recommendations [ 10 , 11 ]. With the emergence of more and more literature about prenatal presentations of genetic disorders, the selection criteria are also widened to include a fetus with increased nuchal translucency (≥6.5 mm) plus another anomaly and isolated non-immune fetal hydrops [ 25 , 26 , 27 , 28 , 29 ]. Besides, the diagnostic yield may also vary widely across different structural abnormalities, as previous studies reported higher yields in multisystem anomalies, isolated skeletal anomalies and isolated brain anomalies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We select the cases with reference to the updated eligibility criteria from overseas programs (e.g., National Health Service (England) [ 25 ]) and professional society recommendations [ 10 , 11 ]. With the emergence of more and more literature about prenatal presentations of genetic disorders, the selection criteria are also widened to include a fetus with increased nuchal translucency (≥6.5 mm) plus another anomaly and isolated non-immune fetal hydrops [ 25 , 26 , 27 , 28 , 29 ]. Besides, the diagnostic yield may also vary widely across different structural abnormalities, as previous studies reported higher yields in multisystem anomalies, isolated skeletal anomalies and isolated brain anomalies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…89 A specific clinical scenario that has arisen in the NIPT era is the management of an isolated increased NT measurement in a pregnant person with a low chance NIPT result. 90 A NT ≥ 3.5 mm is associated with a variety of conditions that are not detectable on NIPT, including atypical chromosome abnormalities, single gene conditions, and structural malformations. Diagnostic testing should therefore be recommended to pregnant patients who have a NT ≥ 3.5 mm at 11-13 weeks gestation, regardless of prior or intended NIPT.…”
Section: Role Of Ultrasound In Non-invasive Prenatal Testingmentioning
confidence: 99%
“…If the NT is increased and/or structural anomalies are found, an invasive test including a microarray analysis or whole‐exome sequencing is more appropriate than NIPT 60 . Performing NIPT before the NT measurement does not allow for the correct identification of these cases and may lead to false reassurance of couples based on the normality of the NIPT results 61,62 . In a study where women with a normal NIPT (for Trisomy 21, 18 and 13) were also offered a first‐trimester scan, an unexpected finding was observed in 3.5% of pregnancies with normal NIPT 63 .…”
Section: First Trimester Screening Strategiesmentioning
confidence: 99%